GREAT GAP BETWEEN CUSTOMERS’ TASTE AND MARKET VARIETY IN THE CAR MARKET IN IRAN - Mousavi, Farhad; Vizvari, Bela (The South African Journal of Industrial Engineering, 2014)
In this paper, types of cars are described by factors, with each factor consisting of different levels. The satisfaction of the customer is determined by the levels of the factors and the price of the car. Two groups of customers with different tastes are identified in the car market in Iran. The two groups cover 82.4 per cent of customers. Based on the values of the factors, the value of each vehicle is obtained for each group. The aim of this research is to obtain a better understanding of customers’ taste, in order to determine the market share of cars and ensure that customers’ needs can be satisfied properly. In this way, companies can develop better strategies and production plans and can increase their market share. The size of each group was determined, as well as their characteristics in terms of gender, age, and education status. Using Tirole’s [27] and Gabszewicz and Thisse’s [12] respective theories, the shares of the car market, according to customers’ demands, were determined. The new method adopted in this study is the generalisation of Tirole’s [27] product differentiation theory to the case in which the pairwise ranking of the products forms an acyclic network and not only a directed path. The estimated demand is compared with the sales data from the last five years. A big gap between the status of the vehicle sales and the customer requirements is observed in the car market in Iran.